Eruptive Activity on the Western Flank of Piton de la Fournaise (La Réunion Island, Indian Ocean): Insights on Magma Transfer, Storage and Evolution at an Oceanic Volcanic Island. (18th October 2019) - Boudoire, G; Brugier, Y -A; Di Muro, A; Wörner, G; Arienzo, I; Metrich, N; Zanon, V; Braukmüller, N; Kronz, A; Le Moigne, Y; Michon, L
Abstract: Petrological and geochemical (major element, trace element, Sr–Nd isotope) data for recent (<5 kyr old) basalts that sporadically erupt on the western flank of Piton de la Fournaise (PdF), one of the most active volcanoes on Earth, allow the tracking of magma transfer and evolution from mantle to crustal depths. In the western peripheral area of PdF we document the broadly synchronous eruptions of (1) primitive olivine and olivine–clinopyroxene transitional basalts with tholeiitic affinity that are closely associated in space with (2) transitional olivine basalts with alkaline affinity, and (3) hybrid lavas, intermediate between the 'alkaline' and the 'tholeiitic' end-members. The composition of the latter overlaps with that of the lavas frequently erupted from the conduit system feeding the main summit cone. AlphaMELTS modelling, and fluid inclusion and clinopyroxene barometry, constrain the conditions of magma storage at 10–30 km, and the ascent of magma from the upper mantle to the shallow crustal plumbing system. Variable degrees of mantle melting, together with minor source heterogeneity and contamination with cumulate-derived partial melts, contribute to the diversity of PdF magmas. However, all these processes do not represent the dominant factors that produce the large variability we found in major element composition. Indeed, the composition of basalts erupted from PdF peripheral centers is strongly controlled by polybaric olivine–clinopyroxene fractionation at pressures higher than 3 kbar. Crystal textures and geochemical modelling suggest that fast magma ascent is critical to prevent clinopyroxene dissolution. Conversely, long-lasting magma stagnation promotes pyroxene resorption and magma differentiation. 'Central' eruptions occurring close to the PdF summit cone emit variably more evolved melts, which result from olivine–clinopyroxene–plagioclase differentiation at intermediate–shallow pressure (<3 kbar and in most cases <1 kbar). Deep and extensive magma mixing before injection into the crustal magma conduit system, located below the summit region, results in the apparent homogeneity of basalts erupted from the central area. As regards 'peripheral' eruptions, deep-seated stagnation of basaltic melts and differentiation at the mantle–crust transition zone ( c . 4 kbar) produces a range of magma compositions. We demonstrate that rapid magma ascent from deep-seated reservoirs can bypass the central plumbing system. The eruptions of these magmas both in the central area and on the densely populated flanks have major consequences in terms of volcanic hazard at PdF.